A comparative study of the volatiles emitted by flowers of three Hedychium species from La Réunion. Issue 1 (2nd January 2023) - Gauvin-Bialecki, Anne; Smadja, Jacqueline
ABSTRACT: With the objective to develop a scent database that could be used for perfume and cosmetics applications, a comparative analysis of the floral profiles close to one hundred odorous flowering plants found in Reunion Island has been undertaken for the last few years in our laboratory. A part of this work relating to three Hedychium species (the well-known H. coronarium but also H. flavescens and H. gardnerianum ) is presented here. To achieve this, the solid-phase microextraction (SPME) on living flowers coupled to GC/MS was used. A total of 53 volatiles were identified belonging to aliphatic ketones, monoterpenes (hydrocarbons and oxygenated), sesquiterpenes (hydrocarbons and oxygenated), phenylpropanoids/benzenoids and miscellaneous. The phenylpropanoid/benzenoid and terpenoid classes were the main volatile classes. ( E )-β-ocimene, linalool, ( E, E )-α-farnesene, ( E )-nerolidol, methyl benzoate, methyl salicylate, ( E )-isoeugenol and indole were the major compounds detected. Results also revealed significant aroma variation among the different flowers.